PROPORTION OF PATIENTS WITH MACULAR HOLE SURGERY WHO WOULD HAVE BEEN FAVORABLE OCRIPLASMIN CANDIDATES: A Retrospective Analysis. Issue 1 (January 2017) - Chaudhary, Khurram; Mak, Michael Y. K.; Gizicki, Robert; Muni, Rajeev H.; Wong, David T.; Altomare, Filiberto; Berger, Alan R.
Abstract : Purpose: To identify favorable ocriplasmin candidates from a cohort of idiopathic full thickness macular hole surgery patients. Methods: The records of patients with full thickness macular hole who underwent pars plana vitrectomy surgery between 2011 and 2015 were reviewed. Clinical data collected included patient demographics, pre- and post-operative Snellen visual acuity, optical coherence tomography findings, and lens status. The authors defined "favorable" ocriplasmin candidates as patients with focal vitreomacular traction, no epiretinal membrane, and hole size ⩽400 μ m. The authors further categorized "optimal" candidates as age ⩽65, phakic, no epiretinal membrane, with focal vitreomacular traction, and hole size ⩽400 μ m. Results: The records of 238 patients were assessed; 30.7% were male while mean age was 68.6 ± 8.3 years. The mean logMAR acuity was 1.2 (Snellen 20/317) preoperatively and 0.90 (Snellen 20/159) postoperatively. Optical coherence tomography findings indicated that 46.5% of the macular holes studied were less than ⩽400 μ m in size, 14.8% had an epiretinal membrane, and 25.3% had vitreomacular traction. A total of 17.7% of study patients were found to be favorable candidates, whereas 3.8% were optimal ocriplasmin candidates. Conclusion: Only a minority of full thickness macular hole surgical candidates in this cohort would be considered favorable ocriplasmin candidates. Abstract : The proportion of patients with idiopathic macular hole surgery who would have been favorable ocriplasmin candidates is unknown. This retrospective review of 238 patients found that only 17.7% of these patients were favorable candidates and 3.8% were optimal candidates for ocriplasmin treatment.